The Concepts of Joy in Georgian and German Languages - Iakobidze, Natia (Actual Problems of Kartvelology, 2013)
Every nation has its own worldview, which depends on the language that nation speaks. The diversity of languages ​​is not only a diversity of symbols, but also a diversity of worldviews. When examining any linguistic unit, the culture and history of the nation must be taken into account. Languages ​​differ from one another primarily in the realm of emotions. Material culture is perceived through the senses, unlike emotions, which are accessible to human consciousness only through language. They have no corresponding objects in the material world. The differentiation of emotions depends on their verbalization. In every language, there are linguistic units that express joy, which can be considered universal, but the expression and evaluation of joy differs in every culture. Joy in Georgian is expressed by the lexeme "sikharuli", which, in addition to inner happiness, also means celebration. Georgian"Lkhini" (celebration) is defined in Sulkhan-Saba Orbeliani's dictionary as joy through eating, drinking, and singing. It is about creating a collective mood. In German, joy is expressed by the following lexemes: Freude, Freudigkeit, Fröhlichkeit, Lustigkeit. Freude and Freudigkeit are more internal, while Fröhlichkeit and Lustigkeit are external. Cheerful and merry people express their joy through singing, dancing, and joking. The expression of joy in Georgian is focused on the social aspect of society and expresses the collective mood, in contrast to German, where joy signifies the inner mood of individuals.